2017
DOI: 10.1159/000485584
|View full text |Cite
|
Sign up to set email alerts
|

SPARCL1, a Novel Prognostic Predictive Factor for GI Malignancies: a Meta-Analysis

Abstract: Background/Aims: Secreted protein acidic and rich in cysteines-like 1 (SPARCL1) is abnormally expressed in gastrointestinal (GI) malignancies. However, the correlation between SPARCL1 expression and the prognosis of patients remains unknown. Therefore, we performed a meta-analysis to investigate the potential value of SPARCL1 as a prognostic predictive marker for GI malignancies. Methods: The PubMed, Embase, EBSCO, CNKI, and Wanfang databases were systematically searched for studies examining SPARCL1 and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Previous analyses of hSPARCL1 expression in human tissues showed a preferential downregulation of expression in neoplastic tissues [5,[8][9][10][11][12][13][14][15]. This is also reflected by recent studies examining the effects of hSPARCL1 on tumorigenesis and metastasis formation [25][26][27][28][29][30]. However, there is still little information on the general expression patterns of SPARCL1 in human and murine tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses of hSPARCL1 expression in human tissues showed a preferential downregulation of expression in neoplastic tissues [5,[8][9][10][11][12][13][14][15]. This is also reflected by recent studies examining the effects of hSPARCL1 on tumorigenesis and metastasis formation [25][26][27][28][29][30]. However, there is still little information on the general expression patterns of SPARCL1 in human and murine tissues.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of eight studies including a total of 2356 patients revealed that its expression is associated with less lymph node and distant metastasis. The negative association between the SPARCL1 expression and poor tumour differentiation indicates the major role of aggressive tumour behavior [20]. In addition, the prognostic impact of SPARCL1 expression in ovarian and prostate cancers has also been reported [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…To date, limited studies have reported that lower SPARCL1 expression suggests poor survival in human malignancies [ 27 32 ]. A meta-analysis revealed that SPARCL1 could predict poor clinical outcomes for gastrointestinal malignancies [ 33 ]. In our study, we pooled four clinical studies to explore the prognostic value of SPARCL1 in CRC.…”
Section: Discussionmentioning
confidence: 99%